SOUTHERN FLOODING AND FOOD PRODUCTION: AN EMPIRICAL STUDY OF FARMER'S MOTIVATION IN THE ERA OF FLOODING - Eke Joy Ndidi, Chijioke- (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
The importance of comprehending community vulnerability to extreme hydrological events has increased as a result of projections of climate change that indicate an increase in the frequency and intensity of climatic hazards like flooding. The present study examined the effect of flooding on farmers' motivation. Two hundred and twenty-five farmers recruited from farming communities in southern Nigeria completed a self-report instrument to ascertain their motivations relative to continuing farming activities in the era of flooding. A cross-sectional design was employed in the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, Version 23). Simple regression was run to test the main hypothesis that flooding would predict farmers' motivation. The analysis demonstrated a statistically significant effect of flooding concerns on the farmers' motivation F (1,223), 21.31 P< .05, with the R2 indicating the independent variable accounted for 22.3% of the variation in farmers' motivation. The present finding contributes to the agricultural literature by revealing the flooding trend as a potential determinant of farmers' low motivations and the increasing low food production.